On the structure of psychoeducational constructs: taxometric analysis and epistemological implications - Stamovlasis, Dimitrios; Vaiopoulou, Julie; Stavropoulou, Georgia; Papagiannopoulou, Theano (Frontiers in Psychology, 2025)
Taxometric analysis (TA) is a technique designed to elucidate the structure of a psychological construct, specifically determining whether the latent variable is categorical (taxon) or dimensional. The taxon hypothesis is significant because the structure of a latent construct influences how we conceptualize, characterize, and measure it, thereby impacting the methodologies employed in both research and practical applications. In this study, data from two separate studies were subjected to TA. Study 1 involves secondary school students (N = 2024) and explores factors such as Achievement Goals and Self-Efficacy within the context of language acquisition. Study 2 examines issues among service teachers (N = 494) and includes variables such as Attitudes, Self-Efficacy, Commitment, and Cognitive and Affective conditions within the framework of STEM education. Given that the taxon hypothesis is tested for the first time using these types of psychoeducational data, Taxometrics is applied in an exploratory manner to provide a deeper understanding of the nature of these constructs. The results of TA are based on a series of indicators that identified cases of dimensional constructs when items from a single dimension were used as input. However, when all elements related to achievement goals and teacher readiness were utilized as input, the results revealed ambiguous latent structures. This emerging ambiguity prompts theoretical and epistemological discourse to explain the findings and advocate for a reevaluation of the nature of latent psychoeducational constructs.